Association of Anthropometric and Lifestyle Parameters with Fitness Levels in Greek Schoolchildren: Results from the EYZHN Program - Arnaoutis, Giannis; Georgoulis, Michael; Psarra, Glykeria; Milkonidou, Anna; Panagiotakos, Demosthenes B.; Kyriakou, Dafni; Bellou, Elena; Tambalis, Konstantinos D.; Sidossis, Labros S. (Frontiers in Nutrition, 2018)
Objective: To evaluate physical fitness (PF) and identify its anthropometric and lifestyle determinants in a sample of Greek schoolchildren. Methods: The study sample consisted of 335,810 schoolchildren (♂: 51.3%, 6-18 years old). Students’ anthropometric parameters and PF levels - assessed via the Euro-fit test battery - were measured by trained physical education teachers and evaluated according to available norms, while their lifestyle habits were assessed through a questionnaire. Results: In all applied PF tests, students’ performance was negatively associated with the presence of obesity and central obesity, defined through international criteria for body mass index and waist to height ratio, respectively. According to multiple logistic regression analysis, the presence of overweight/obesity [odds ratio (OR): 4.43, 95% confidence interval (CI): 3.98-4.93)], low adherence to the MD (KIDMED ≤3) (OR: 1.27, 95% CI: 1.09-1.48), and increased time spent in sedentary activities (>2 hours per day) (OR: 1.16, 95% CI: 1.03-1.29), were positively associated with poor PF, after adjusting for age and sex. In contrast, for every one day increase in the weekly frequency of engagement in athletic activity, the probability of poor PF decreased by 26% (OR: 0.74, 95% CI: 0.72-0.77). In a similar model, the presence of central obesity emerged as an even stronger possible predictor of poor PF (OR: 5.20, 95% CI: 4.66-5.78), compared to the presence of general obesity. Conclusion: Higher general or abdominal adiposity, as well as the adoption of a low-quality diet and a sedentary lifestyle, are strongly associated with low PF levels during childhood.